2018
DOI: 10.1007/s10948-018-4707-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fe Substitution on the Physical Properties of La0.62Er0.05Ba0.33Mn1−xFexO3(x = 0.00, 0.05 and 0.15)

Abstract: Morphology, magnetic and magnetocaloric properties of La 0.62 Er 0.05 Ba 0.33 Mn 1−x Fe x O 3 (x = 0.00, 0.05 and 0.15) were experimentally investigated. Solid-state reaction method was used in the preparation of the samples. The microstructure of the samples was determined by scanning electron microscopy (SEM). From the XRD study, it has been found that all samples are single-phased and crystallized in the rhombohedral structure with the R3-c space group. For x = 0.05 and 0.15, a steep drop of zero field-cool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
0
0
0
Order By: Relevance
“…The findings are consistent with a prior study that reported a similar suggestion [27,29,30]. 5 dominant effect of the super-exchange (SE) mechanism, which involves Fe 3+ -Fe 3+, Mn 3+ -Mn 3+ and Mn 4+ -Mn 4+ [24]. Furthermore, other research stated a similar suggestion as Fe 3+ doped in Pr0.67Sr0.16Ca0.17Mn0.75Fe0.25O3 manganite and reported that Fe 3+ ion does not participate in the double exchange (DE) mechanism [3].…”
Section: Electrical Propertiessupporting
confidence: 92%
See 3 more Smart Citations
“…The findings are consistent with a prior study that reported a similar suggestion [27,29,30]. 5 dominant effect of the super-exchange (SE) mechanism, which involves Fe 3+ -Fe 3+, Mn 3+ -Mn 3+ and Mn 4+ -Mn 4+ [24]. Furthermore, other research stated a similar suggestion as Fe 3+ doped in Pr0.67Sr0.16Ca0.17Mn0.75Fe0.25O3 manganite and reported that Fe 3+ ion does not participate in the double exchange (DE) mechanism [3].…”
Section: Electrical Propertiessupporting
confidence: 92%
“…The significant decrease in T C could be attributed to a weakening of ferromagnetic (FM) interaction caused by an enhancement of antiferromagnetic (AFM) ordering with Fe substitution [3]. A few reports similar finding regarding Fe substitution at Mn-site, suggesting that the weakening of FM interaction could also be due to the reduction of the Mn 3+ /Mn 4+ ratio [23,24].…”
Section: Structural Propertiesmentioning
confidence: 79%
See 2 more Smart Citations